miRNAs in bladder cancer: Its functional contributions and therapeutic potential. - Muhammed Al-Rubaiy; Ali Al-Rubaiy; Syed A Aziz (International Journal of Endorsing Health Science Research, 2025)
Background: Bladder cancer (BC) is one of the most prevalent malignancies worldwide, with a significant burden on healthcare systems due to its high recurrence rates and invasive diagnostic procedures. While cystoscopy and urine cytology remain the gold standards for BC diagnosis, they have notable limitations in sensitivity and invasiveness. MicroRNAs (miRNAs), small non-coding RNAs involved in post-transcriptional gene regulation, have emerged as promising biomarkers and therapeutic targets in BC. This systematic review explores the role of miRNAs in BC pathogenesis, diagnosis, prognosis, and therapeutic applications, with a focus on their molecular mechanisms and clinical potential. Methodology: A comprehensive literature review was conducted using PubMed, covering studies from January 2020 to August 2023. Inclusion criteria encompassed original research articles, systematic reviews, and meta-analyses on miRNAs in BC. Exclusion criteria included non-human studies, non-urothelial malignancies, and studies with insufficient mechanistic insights. Data were extracted regarding miRNA functional roles, diagnostic potential, therapeutic implications, and interactions within the tumor microenvironment. Results: Multiple miRNAs were identified as key regulators in BC progression. Exosomal miR-217 inhibits ferroptosis, promoting tumor survival, while miR-3960 and miR-490-3p act as tumor suppressors by targeting oncogenic proteins. Cuproptosis-related miRNAs were linked to BC prognosis and immune modulation. Additionally, miR-146a-5p, derived from cancer-associated fibroblasts, enhances chemoresistance and tumor stemness. Several miRNA-based diagnostic panels demonstrated high sensitivity and specificity in distinguishing BC from benign conditions. Therapeutically, restoring tumor-suppressive miRNAs or inhibiting oncogenic miRNAs holds potential for personalized medicine in BC treatment. Conclusion: MiRNAs play a crucial role in BC pathogenesis, serving as both oncogenic drivers and tumor suppressors. Their stability in body fluids positions them as promising non-invasive biomarkers for early detection and disease monitoring. Furthermore, miRNA-based therapeutic strategies offer new avenues for targeted BC treatments.